Facile construction of polyoxometalate-modified polyaryletherketone-based hybrid membranes with enhanced proton conductivity - Bo Hu; Qiuchen Du; Yang Yang; Dengdeng Li; Jiawang Fu; Bailing Liu; Hong-Ying Zang; Yangguang Li; Haiming Xie; Zhongmin Su (Polyoxometalates)
The development of novel proton exchange membranes (PEMs) with high proton conductivity and good mechanical performance as alternatives to Nafion is crucial. Polyoxometalates (POMs), a type of solid-state nanoclusters, possess high proton conductivity and good structural stability, making them suitable functional inorganic fillers to improve the performance of PEMs. Herein, the Keggin-type POM H3PW12O40·nH2O (PW12) was introduced into sulfonated polyaryletherketone (SPAEK) with closely packed and flexible side chains to construct hybrid membranes (SPAEK-PW12-x%, x = 5, 10, 13, 15). Because of its structural characteristics, the nanosized PW12 induced precise hybridization of the nanophase structure of this ionomeric polymer and the formation of proton transport channels. Additionally, the hydrogen-bonding networks formed by PW12 and sulfonic acid groups increased the proton conductivity and mechanical strength of the resulting hybrid PEMs and improved the close-packed structure of the PEMs to achieve an appropriate balance between conductivity and fuel permeation. In particular, SPAEK-PW12-13% achieved an enhanced proton conductivity of 0.167 S∙cm−1 at 80 °C, which was 2.2 times greater than that of the pristine membrane. Moreover, the mechanical properties, chemical stability, resistance to methanol penetration, and ionic selectivity of the hybrid membrane were significantly improved upon addition of a moderate amount of PW12. This work provides an approach for the design and development of new-generation organic–inorganic hybrid membranes through precise hybridization of POMs.